Current levels and trends of selected EU Water Framework Directive priority substances in freshwater fish from the German environmental specimen bank. (September 2016) - Fliedner, Annette; Lohmann, Nina; Rüdel, Heinz; Teubner, Diana; Wellmitz, Jörg; Koschorreck, Jan
Abstract: Under the German environmental specimen bank programme bream ( Abramis brama ) were sampled in six German rivers and analysed for the priority hazardous substances dicofol, hexabromocyclododecane (HBCDD), hexachlorobenzene (HCB), hexachlorobutadiene (HCBD), heptachlor + heptachlor epoxide (HC + HCE), polybrominated diphenylethers (PBDEs), polychlorinated dibenzo-p-dioxins and -furans and dioxin-like polychlorinated biphenyls (PCDD/Fs + dl-PCBs), and perfluorooctane sulfonic acid (PFOS). The aim was to assess compliance with the EU Water Framework Directive environmental quality standards for biota (EQSBiota ) for the year 2013, and to analyse temporal trends for those substances that are of special concern. General compliance was observed for dicofol, HBCDD and HCBD whereas PBDEs exceeded the EQSBiota at all sites. For all other substances compliance in 2013 varied between locations. No assessment was possible for HC + HCE at some sites where the analytical sensitivity was not sufficient to cover the EQSBiota . Trend analysis showed decreasing linear trends for HCB and PFOS at most sampling sites between 1995 and 2014 indicating that the emission reduction measures are effective. Mostly decreasing trends or constant levels were also observed for PCDD/Fs and dl-PCBs. In contrast, increasing trends were detected for PBDEs and HBCDD which were especially pronounced at one Saar site located downstream of the industries and conurbation of Saarbrücken and Völklingen. This finding points to new sources of emissions which should be followed in the coming years. Graphical abstract: PCDD/Fs and dl-PCB in muscle of bream from German rivers. Symbols signify compliance (green) or exceedance (red) of the EQSBiota (0.0065 μg WHO2005-TEQ*kg −1 wet weight). Highlights: Archived annual bream samples were analysed for 8 priority substances/groups. General EQSBiota compliance was observed for dicofol, HBCDD and HCBD in 2013. PBDEs exceeded the quality standard at all sites during the period 1995–2014. HCB and PFOS in bream decreased at most sampling sites since 1995. PBDEs and HBCDD levels strongly increased in bream from one Saar site. Abstract : Mostly decreasing trends of concentrations of several priority hazardous substances in fish indicate that the water quality of German freshwaters is improving; however, fish burdens of some compounds are still not compliant with environmental quality standards.